118k views
5 votes
3(2x-1)=5x+3+7x I do t get this cause I’m stupid

User Gmetal
by
5.7k points

1 Answer

2 votes

Answer:

x = -1

Explanation:

Solve for x:

3 (2 x - 1) = 7 x + 5 x + 3

Grouping like terms, 7 x + 5 x + 3 = (5 x + 7 x) + 3:

3 (2 x - 1) = (5 x + 7 x) + 3

5 x + 7 x = 12 x:

3 (2 x - 1) = 12 x + 3

Expand out terms of the left hand side:

6 x - 3 = 12 x + 3

Subtract 12 x from both sides:

(6 x - 12 x) - 3 = (12 x - 12 x) + 3

6 x - 12 x = -6 x:

-6 x - 3 = (12 x - 12 x) + 3

12 x - 12 x = 0:

-6 x - 3 = 3

Add 3 to both sides:

(3 - 3) - 6 x = 3 + 3

3 - 3 = 0:

-6 x = 3 + 3

3 + 3 = 6:

-6 x = 6

Divide both sides of -6 x = 6 by -6:

(-6 x)/(-6) = 6/(-6)

(-6)/(-6) = 1:

x = 6/(-6)

The gcd of 6 and -6 is 6, so 6/(-6) = (6×1)/(6 (-1)) = 6/6×1/(-1) = 1/(-1):

x = 1/(-1)

1/(-1) = -1:

Answer: x = -1

User Housni
by
5.5k points